Reflexiones docentes acerca de las concepciones sobre la evaluación del aprendizaje y su influencia en las prácticas evaluativas - Flórez Nisperuza, Elvira Patricia; Páez, Julio; Fernández, Carlos Mario; Salgado, Jhan Freddy (Revista Científica, 2019)
This article deals with the evaluation of learning and its influence on evaluative practices, based on the recognition of the conceptions of students and teachers involved in the educational act, based on research and opinions of different authors on the subject. It is detailed in the research findings that highlight the reflections built by a team of teachers and teachers in training from the Department of Natural Sciences and Environmental Education of the University of Córdoba -Colombia, within the framework of the research project "characterization of evaluation practices in the Educational Institutions of the Department of Córdoba". A search and identification process of documentary information is carried out in databases, categorized and analyzed through rubric and glossary instruments based on a heuristic method that led to the preparation, selection and search, allowing obtaining characterization criteria for each investigation. And arriving at a hermeneutic phase, in which documented and contrasted reflections were made to reach conclusions. Finally, it is established that the conceptions of teachers and students have reciprocal relevance, where teachers are in charge of assessing the evaluation process and determine if significant learning has been achieved; and students, from the conception of knowledge, act as passive or active agents in the evaluation process. In addition, the evaluation is taken more than as an instrument, as a means to determine the weaknesses and strengths that both the teacher and the student have.